2021
DOI: 10.4236/ojee.2021.102004
|View full text |Cite
|
Sign up to set email alerts
|

PV-Wind-Diesel System for Energy Supply on Remote Area Applied for Telecommunication Towers in Comoros

Abstract: The Comoros is an archipelago in the Indian Ocean located in the Mozambique Channel between the African continent and Madagascar. Geographically Comoros is composed of four islands: Grande Comores, Anjouan, Mohéli and Mayotte (under French administration). Apart from Mayotte, the others three independent islands commonly known as the Union of the Comoros are suffering from energy stress since their independence year 1975 until nowadays. The energy supplied and distributed by the national electricity company, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…$ 0.506/kWh at a load of 83 kWh/day; $ 0.552/kWh at a load of 55 kWh/day; $ 0.839/kWh at a load of 22.7 kWh/day). A similar study was carried out by Maoulida et al (2021) specific to Comoros and they suggested that all the renewable energy combinations are better LCOE over DG and battery based solution. Kaur et al (2020) have studied the application of renewable energy-based DC microgrid for powering telecom towers in remote areas.…”
Section: Pv- Wind-and Battery-based Systemmentioning
confidence: 74%
“…$ 0.506/kWh at a load of 83 kWh/day; $ 0.552/kWh at a load of 55 kWh/day; $ 0.839/kWh at a load of 22.7 kWh/day). A similar study was carried out by Maoulida et al (2021) specific to Comoros and they suggested that all the renewable energy combinations are better LCOE over DG and battery based solution. Kaur et al (2020) have studied the application of renewable energy-based DC microgrid for powering telecom towers in remote areas.…”
Section: Pv- Wind-and Battery-based Systemmentioning
confidence: 74%
“…The cash flow is presented in Fig. 9 and we observe that, our system is cost effective because for 25 years there will be more loss that supplies fuel to the generator and a spare but the project will have a huge cost to the last year of its installation [10]. The replacement of material must take place from the 20 th of year of the project.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of the site was based on the availability of meteorological data. So we give the diagrams below the annual evolution of the main climatic characteristics of the chosen site [10][11][12][13]: Fig. 2 representing the temperature is recorded from the month of August with a temperature of about 29°C.…”
Section: Data Of the Chosen Location Site And Climatic Characteristicsmentioning
confidence: 99%
“…Research conducted in Comoros revealed that a standalone system incorporating PV, wind energy, and BESS is the most economically efficient choice with minimal environmental consequences (no GHG emissions). However, the cost of battery storage still poses a challenge (Maoulida et al, 2021). (Bahgaat, 2023) which is a study conducted in Egypt using a stand-alone energy system with energy storage.…”
Section: Case Studiesmentioning
confidence: 99%